The role of macrophage ion channels in the progression of atherosclerosis - Wu, Xin; Singla, Sidhant; Liu, Jianhua J.; Hong, Liang (Frontiers in Immunology, 2023)
Atherosclerosis is a complex inflammatory disease that affects the arteries and can lead to severe complications such as heart attack and stroke. Macrophages, a type of immune cell, play a crucial role in atherosclerosis initiation and progression. Emerging studies revealed that ion channels regulate macrophage activation, polarization, phagocytosis, and cytokine secretion. Moreover, macrophage ion channel dysfunction is implicated in macrophage-derived foam cell formation and atherogenesis. In this context, exploring the regulatory role of ion channels in macrophage function and their impacts on the progression of atherosclerosis emerges as a promising avenue for research. Studies in the field will provide insights into novel therapeutic targets for the treatment of atherosclerosis.